Optimum Utilization of Steel Reinforcement and Its Management: Enhancing Steel Utilization and Yard Management for Successful Construction Projects (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Optimum utilization of steel in construction industry optimize by means of standardization of BBS Techniques and managing steel yard to reduce construction steel wastage. BBS techniques can be improve by utilizing standard software like Autodesk Rivet, VICO, Naviswork. Steel yard management technique should be improve with improving lay down yard management and using advance Autodesk software for BIM models for effective implementation of successful construction project.